Peningkatan Pengetahuan dan Kemampuan Penanggulangan Bencana Banjir melalui Sosialisasi di Guru dan Siswa di Kota Bekasi - Dodi Rahmat Setiawan; Yusup Rachmat Hidayat; Rousdy Safari Tamba; Suparman Suparman; Zulkifli Zulkifli (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
According to Law Number 24 of 2007, Flood is an event or condition where an area or land is submerged due to an increased volume of water. The impact of floods often causes human casualties, physical losses, property losses, social, economic losses, environmental damage, infrastructure damage, and psychological impacts. Floods occur in almost all parts of Indonesia, especially during the rainy season in areas with high rainfall intensity. AL-Fajar Islamic College, Jatiasih District, Bekasi City, West Java Province is one of the educational facilities that has and is often affected by floods in the area.The problem of limited information and public knowledge about flood disaster management is a vulnerability factor for the risks and impacts of the flood disaster itself. This requires socialization of flood management for communities affected by flood disasters. The purpose of this activity is to increase the knowledge and ability of the community in dealing with and reducing disaster risk. The results of this activity are believed to provide increased knowledge, ability and preparedness in dealing with threats and minimizing the impact of flood disasters.